Multisystem inflammatory syndrome in children characterized by enhanced antigen-specific T-cell expression of cytokines and its reversal following recovery - Pavan Kumar, Nathella; Abbas, Kadar M.; Renji, Rachel M.; Venkataraman, Aishwarya; Nancy, Arul; Varadarjan, Poovazhagi; Selladurai, Elilarasi; Sangaralingam, Thankgavelu; Selvam, Ramya; Thimmaiah, Akshith; Natarajan, Suresh; Ramasamy, Ganesh; et al. (Frontiers in Pediatrics, 2023)
Background: Multisystem Inflammatory Syndrome in Children (MIS-C) is considered to be a post-infectious complication of COVID-19. T cell responses in MIS-C children have not been well-studied. Methods: We aimed to study the immune responses in children with MIS-C in comparison to children with acute COVID-19 and children with other infections. Whole blood was stimulated with SARS-CoV-2-specific antigens and flow cytometry was performed to examine CD4+ and CD8+ T cell responses. Results: Children with MIS-C had higher frequencies of CD4+ and CD8+ T cells expressing cytokines at baseline and upon SARS-CoV-2 antigen-specific stimulation in comparison to children with COVID-19 and/or other infections. COVID-19 children also exhibited higher frequencies of CD4+ and CD8+ T cells expressing cytokines at baseline and upon SARS-CoV-2 antigen-specific stimulation in comparison to children with other infections. At 6 to 9 months following treatment and recovery, this enhanced response against SARS-CoV-2 antigens was down modulated in MIS-C. Conclusion: Our study, therefore, provides evidence of enhanced activation of CD4+ and CD8+ T cell responses in MIS-C in children and reversal following recovery